Educational Management Model Based on Religious and Cultural Values at Ar Rahmah College Student Pesantren Surabaya - Shobikhul Qisom; Muh. Syahril Sidik Ibrahim; Isa Saleh; Agus Salim Panjaitan (Mimbar Agama Budaya, 2025)
This study examines the development of a religious- and culture-based educational management model implemented at the Ar Rahmah Student Pesantren in Surabaya. The central problem addressed is the lack of integrated educational systems in many Islamic institutions, which tend to separate academic learning, spiritual formation, and practical competence, leaving graduates who fall short of contemporary needs for mosque leadership. Using a descriptive qualitative method, data were collected through interviews, participatory observation, and document analysis, and were processed using the interactive model of Miles, Huberman, and Saldaña. The findings show that Ar Rahmah successfully integrates undergraduate studies, a 30-juz tahfidz program, and mosque management practice into a 24-hour learning ecosystem supported by pesantren culture and transformational leadership. The model strengthens students’ spirituality, discipline, and professional competence. The study recommends further empirical evaluation involving alum career outcomes. In conclusion, the Ar Rahmah model represents an effective and replicable form of values-based Islamic educational management.